Arkeologi Pengetahuan atas Diskursus Dispensasi Nikah dalam Hukum Keluarga Islam Kontemporer di Indonesia - ririn; Karsidi; Abdul Matin Bin Salmand (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the discourse of marriage dispensation in contemporary Islamic family law in Indonesia through the archaeology of knowledge approach. The research focuses on identifying discursive formations, epistemes shaping legal knowledge, power relations in the production of legality, and epistemological reconstruction of marriage dispensation within Islamic legal perspectives. This qualitative library research analyzes legal regulations, religious court decisions, and contemporary academic literature. The findings reveal that marriage dispensation is shaped by three main discourses: child protection, preventive morality, and judicial pragmatism. Legal knowledge regarding marriage dispensation is constructed through contestation between classical fiqh episteme, modern child protection paradigms, and contextual judicial rationality. Power relations among the state, judges, religious authorities, and society produce regimes of truth that determine the legality of marriage dispensation. This study recommends an epistemological reconstruction grounded in integrative maqāṣid al-sharī‘ah, empirical interdisciplinary approaches, and child centered protection to achieve substantive justice within Indonesian Islamic family law.